2020
DOI: 10.1038/s41598-020-64357-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Neonatal Mortality in Preterm Newborns in The Extreme South of Brazil

Abstract: Neonatal mortality still remains a complex challenge to be addressed. In Brazil, 60% of neonatal deaths occur among preterm infants with a gestational age of 32 weeks or less (≤32w). The aim of this study was to evaluate the factors involved in the high mortality rates among newborns with a gestational age ≤32w in a socioeconomically developed southern city in Brazil. Data on retrospective births and deaths (2000-2014) were analyzed from two official Brazilian national databases. The risk of neonatal death for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
1
3
0
1
Order By: Relevance
“…Tietzmann et al noted a similar relationship between the number of antenatal visits and neonatal mortality, noting that mothers who had less than four antenatal visits had a higher incidence of neonatal mortality, (OR: 1.21 [95% Cl 1.05-1.40)]. 19 It must be noted that while the odds were greater than one in this study, as in ours, it did not approach the threshold for significance. Furthermore, our study showed that neonates of mothers who had a previous miscarriage were not at an increased risk of death (OR: 0.66 [95% Cl 0.39-1.11]).…”
Section: Discussionsupporting
confidence: 71%
“…Tietzmann et al noted a similar relationship between the number of antenatal visits and neonatal mortality, noting that mothers who had less than four antenatal visits had a higher incidence of neonatal mortality, (OR: 1.21 [95% Cl 1.05-1.40)]. 19 It must be noted that while the odds were greater than one in this study, as in ours, it did not approach the threshold for significance. Furthermore, our study showed that neonates of mothers who had a previous miscarriage were not at an increased risk of death (OR: 0.66 [95% Cl 0.39-1.11]).…”
Section: Discussionsupporting
confidence: 71%
“…This sample studied had a mortality rate similar to that in another study conducted in Brazil using data from the Live Birth Information System (Sistema de Informações de Nascidos Vivos) and from the Mortality Information System (Sistema de Informações de Mortalidade) of Porto Alegre, including preterm infants. The study found that neonatal death was 21.64% and the neonatal mortality rate for this group tended to decrease, with a total of 1845 infants who died during the first 27 days of life, with 21% of deaths occurring on the birthday, 45% between days 1 and 6, and 33% between days 7 and 27 45 …”
Section: Discussionmentioning
confidence: 97%
“…This finding agrees with the current body of literature that reports male neonates to have a higher risk of death than female neonates. Evidence showed that male sex neonates are disadvantageous to survive in cases of low birth weight, premature birth, and multiple births than their equivalent female neonates [71][72][73][74][75][76][77][78].…”
Section: Discussionmentioning
confidence: 99%